2006
DOI: 10.1111/j.1524-4725.2006.32052.x
|View full text |Cite
|
Sign up to set email alerts
|

Injection Necrosis of the Glabella: Protocol for Prevention and Treatment After Use of Dermal Fillers

Abstract: Injection necrosis in the glabellar region may be prevented by knowledge of the local anatomy and an understanding of its pathophysiology and treated by a suggested protocol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
125
1
6

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(132 citation statements)
references
References 14 publications
0
125
1
6
Order By: Relevance
“…However, the greatest shortcoming of these synthetic fillers is that they are recognized as a foreign substance by the body, which can cause immune rejection or a granulomatous response. Several studies have reported that these fillers were biocompatible, but other studies have shown a risk of adverse reactions [3][4][5][6]. Moreover, when the area to be corrected is wider, a large amount of filler is required, and this presents limitations due to cost.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the greatest shortcoming of these synthetic fillers is that they are recognized as a foreign substance by the body, which can cause immune rejection or a granulomatous response. Several studies have reported that these fillers were biocompatible, but other studies have shown a risk of adverse reactions [3][4][5][6]. Moreover, when the area to be corrected is wider, a large amount of filler is required, and this presents limitations due to cost.…”
Section: Discussionmentioning
confidence: 99%
“…NUMBER 3. OCTOBER 2017 ing, encapsulation, and granuloma formation, as well as chronic or delayed infections [3][4][5][6]. For this reason, doctors have been searching for autologous sources for soft tissue augmentation.…”
Section: Introductionmentioning
confidence: 99%
“…Hyaluronidase, by quickly breaking down the hyaluronic acid polymer, is able to reduce the risk of skin necrosis secondary to vascular compression if injected early, according to the medical literature [6][7][8]. Unfortunately, injection after 24 hours has been shown to be rather inefficient.…”
Section: Vascular Compression and Occlusion And The Risk Of Necrosismentioning
confidence: 99%
“…Collagen, HA and poly-L-lactic acid can induce granulomatous response, which in some cases can be asymptomatic or manifest as erythema, swelling or nodule formation [10,11,12]. Circulation impairment caused by vascular compression and leading to necrosis or vision loss results from filler administration in the problematic regions or "danger zones" like glabella area, cheeks, nasal ala, peri-oral or temporal area [13,14,15].…”
Section: Artificial Fillers and The Adverse Events Of Their Usementioning
confidence: 99%